Damping correction formula considering the period‐dependent characteristics of the design response spectra of long‐period ground motions for the hypothetical Nankai Trough earthquake: An investigation of the simplified spectra and waveform example provided by the Ministry of Land, Infrastructure, Transport and Tourism - Masahito Kobayashi; Yuto Kataoka (Japan Architectural Review, 2020)
Abstract In June 2016, the Ministry of Land, Infrastructure, Transport and Tourism in Japan announced a countermeasure against the Nankai Trough’s long‐period ground motions. However, the response spectrum method provided in the Ministry of Construction notification Vol. 2009 was not included in the countermeasure because it could not reflect the influence of long‐period ground motions. Therefore, this paper proposes a damping correction formula for long‐period ground motions considering the period‐dependent characteristics of the earthquake response spectra for the design. The applicability of the proposed damping correction formula to seismically isolated buildings is verified by comparing the result by the response spectrum method using this formula with those of a time‐history analysis using the single‐degree‐of‐freedom models.